2020
DOI: 10.3389/fcell.2020.00872
|View full text |Cite
|
Sign up to set email alerts
|

ASPH Regulates Osteogenic Differentiation and Cellular Senescence of BMSCs

Abstract: Osteogenesis and senescence of BMSCs play great roles in age-related bone loss. However, the causes of these dysfunctions remain unclear. In this study, we identified a differentially expressed ASPH gene in middle-aged and elderly aged groups which were obtained from GSE35955. Subsequent analysis in various databases, such as TCGA, GTEx, and CCLE, revealed that ASPH had positive correlations with several osteogenic markers. The depletion of mouse Asph suppressed the capacity of osteogenic differentiation in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…GSK3β is widely recognized as a downstream target of AKT 20 , and previous studies have shown that inhibition of ASPH enzymatic activity leads to increased GSK3β phosphorylation, which promotes tumor cell senescence 21 , 22 . This interaction was also examined in our study, but ASPH inhibitors did not induce GSK3β phosphorylation, suggesting that they may not induce senescence in the cell lines we examined.…”
Section: Resultsmentioning
confidence: 99%
“…GSK3β is widely recognized as a downstream target of AKT 20 , and previous studies have shown that inhibition of ASPH enzymatic activity leads to increased GSK3β phosphorylation, which promotes tumor cell senescence 21 , 22 . This interaction was also examined in our study, but ASPH inhibitors did not induce GSK3β phosphorylation, suggesting that they may not induce senescence in the cell lines we examined.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, bone marrow mesenchymal stem cells (BMSCs) have the potential to differentiate into various types of cells, including osteoblast, and are found in various tissues including bone marrow, adipose tissue, umbilical cord blood, and cancellous bone [ 32 ]. Because of its high proliferation capacity, it is possible to directly perform cell transplantation or implantation on biological material to repair the defect of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression analysis was performed between the two groups of camels using the DESeq2 package in R (version 4.2.1), based on negative binomial distribution. Considering previous studies ( 19 , 20 ) and our specific experimental situation, adjusted p -values ( p adjust ) < 0.01 and |log2FoldChange| >2 were established as the thresholds for significance. p -values were adjusted for multiple testing using the Benjamini and Hochberg methods.…”
Section: Methodsmentioning
confidence: 99%